#TITLE_ALTERNATIVE# - PERMANA KUSUMAWIANGGA (NIM: 10209074), RENADI
Energy consumption is increasing over time. One of the factors that affect the use of the energy supplied is energy wastage. Energy wastage caused by poor installation or power tools that turn on while not in use. In order to determine the performance of the electricity usage is by using energy monitoring system. However, the price of existing energy monitoring systems on the market are still relatively expensive, so only few people that use existing energy monitoring systems. Data – data which obtained from energy monitoring system will be analyzed which will then determine the steps taken to make a saving. One of the austerity measures is to use home automation system. However, existing automation systems market is still expensive, so many people doesn’t to use the home automation systems. The authors use a new communication protocol that is lightweight so that it can be used by low-power microcontroller and power. So the price for energy monitoring systems and home automation can be suppressed